Quantitative effective atomic number imaging using simultaneous x-ray absorption and phase shift measurement - Mukaide, Taihei; Watanabe, Masatoshi; Takada, Kazuhiro; Iida, Atsuo; Fukuda, Kazunori; Noma, Takashi (Applied physics letters, 2011)
A scanning type x-ray imaging system which measures the absorption and differential phase shift in a material quantitatively and simultaneously has been developed. The absorption and differential phase are used to obtain the effective atomic number of organic material samples which closely reflects their chemical composition. An effective atomic number map of polymer fibers has been obtained. The experimentally obtained effective atomic numbers of these polymers agree well with the corresponding calculated values.